Evaluating the association of COVID-19 restrictions on discharge planning and post-discharge outcomes in the community hospital and Singapore regional health system - Chia, Shermain; Xia, Jiawen; Kwan, Yu Heng; Lim, Zhui Ying; Tan, Chuen Seng; Low, Sher Guan; Xu, Bangyu; Loo, Yu Xian; Kong, Lai Yee; Koh, Chee Wai; Towle, Rachel Marie; Lim, Su Fee; et al. (Frontiers in Health Services, 2023)
Objectives The COVID-19 is a global health issue with widespread impact around the world, and many countries initiated lockdowns as part of their preventive measures. We aim to quantify the duration of delay in discharge to community from Community Hospitals, as well as quantify adverse patient outcomes post discharge pre and during lockdown period. Design and methods We conducted a before-after study comparing the length of stay in Community Hospitals, unscheduled readmissions or Emergency Department attendance, patients' quality of life using EQ5D-5l, number and severity of falls, in patients admitted and discharged before and during lockdown period. Results The average length of stay in the lockdown group (27.77 days) were significantly longer than that of the pre-lockdown group (23.76 days), p = 0.003. There were similar proportions of patients with self-reported falls post discharge between both groups. Patients in the pre-lockdown group had slightly better EQ-5D-5l Index score at 0.55, compared to the lockdown study group at 0.49. Half of the patients in both groups were referred to Community Care Services on discharge. Conclusion Our study would help in developing a future systematic preparedness guideline and contingency plans in times of disease outbreak and other similar public health emergencies.